2003
DOI: 10.1093/pubmed/fdg060
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence estimates for chronic diseases in Italy: exploring the differences between self-report and primary care databases

Abstract: The difference between population and primary care morbidity is affected by disease under investigation and patients' demographic characteristics. Therefore, in choosing the more cost-effective approach to collect data such evidence should be taken into account, and results should be interpreted with great caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
109
1
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 9 publications
7
109
1
7
Order By: Relevance
“…First, we identified the patients with evaluable BP level (that is, subjects with recorded BP values in 2005) and those with controlled (o140/90 mm Hg) or noncontrolled (X140/90 mm Hg) BP; then, we examined the prescription pattern and the mean BP values according to the risk level (High risk vs non-high risk) and the hypertension classification (grades according to the guidelines), 7 both in controlled and non-controlled patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we identified the patients with evaluable BP level (that is, subjects with recorded BP values in 2005) and those with controlled (o140/90 mm Hg) or noncontrolled (X140/90 mm Hg) BP; then, we examined the prescription pattern and the mean BP values according to the risk level (High risk vs non-high risk) and the hypertension classification (grades according to the guidelines), 7 both in controlled and non-controlled patients.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of the information gathered has been assessed in earlier studies. 6,7 In Italy, all the citizens are registered with a GP or with a Paediatrician, depending on their age. All the 'life saving' drugs are reimbursed by the National Health Service and, as far as hypertension is concerned, almost all the prescription are filled by GPs.…”
Section: Methodsmentioning
confidence: 99%
“…Completeness and accuracy of information are assessed by running a set of queries (quality indicators) used to generate a composite score ranging from 0-1. Only physicians (n=700) reaching a composite quality score.0.7 were included in epidemiologic studies (12,13), and the validity of the data has been previously shown (14)(15)(16).…”
Section: Methodsmentioning
confidence: 99%
“…20 The HSD contains data from the computer-based patient records from a selected group of GPs distributed across Italy who voluntarily agreed to collect data for the database and attend specified training courses. 20 The database contains information on the age, gender and identification of the patient, and GP registration information, which is linked to the prescription information, clinical events and diagnoses, hospital admission and causes of death. All diagnoses are coded according to the International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM).…”
Section: Health Search/thales Database (Hsd)mentioning
confidence: 99%
“…To be included in the study, GPs needed to be registered with the database for at least 1 year and meet standard quality criteria pertaining to the levels of coding, prevalence of well-known diseases and mortality rates. 20,21 The HSD complies with European Union guidelines on the use of medical data for research. The HSD has been the source for a number of peer-reviewed publications on the prevalence of disease conditions, 21,22 drug safety 23 and prescription patterns [24][25][26][27][28] in Italian primary care.…”
Section: Health Search/thales Database (Hsd)mentioning
confidence: 99%